Hubungan Dukungan Keluarga dengan Resiliensi Pasien Kejadian Perundungan di Poli Sub Spesialis (PSS) RSJ Dr. Radjiman Wediodiningrat Lawang: Sebuah Studi Korelasional - Rina Mustikasari; Dina Dewi Sartika Lestari; Muhammad Soenarto (Poltekkes Kemenkes Malang, 2025)
Bullying is the psychological or physical suppression that harms someone who has less power which can have a negative impact. Bullying resilience is the process of adaptating and coping someone who experiences negative treatment from others in order to be able to escape from a stressful circumstance. Family support can help someone experience the negative effects of bullying and strengthen resilience because of the importance of patients with bullying to recover from their condition. This study aims to determine the relationship between family support and patient resilience in bullying incidents at The Sub Specialist Clinic for Children and Adolescent in RS Radjiman Wediodiningrat Lawang. The method used was observational and a cross-sectional approach with purposive sampling techniques with a total of 47 families and patients with bullying events. Results: The p-value (0.942) was greater than alpha (0.05), indicating that there was no significant relation between family support and patient resilience to bullying events. In addition, pearson's product moment (r) correlation coefficient of 0.011 indicates a very low level of link between family support and resilience levels. It concludes that a weak relationship in the form of changes in family support has a weak impact on patient resilience bullying events and insignificant relationships.